2000
DOI: 10.1007/s00006-000-0001-3
|View full text |Cite
|
Sign up to set email alerts
|

The Four-Dimensional Hyperbolic Spherical Harmonics

Abstract: In the four-dimensional hyperbolic space, we can derive Euler formula and establish the hyperbolic spherical polar coordinate and the hyperbolic spherical harmonics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Considerations of a non-relativistic hyperbolic Hilbert space with respect to the Born formula have been given by Kocik [18], Khrennikov [19,20], and Rochon and Tremblay [21]. Xuegang et al investigated the Dirac wave equation, Clifford algebraic spinors, a hyperbolic Hilbert space, and the hyperbolic spherical harmonics in hyperbolic spherical polar coordinates [22,23,24]. The hypercomplex numbers, and the geometries generated by these numbers, have been investigated by Catoni et al [25].…”
Section: Introductionmentioning
confidence: 99%
“…Considerations of a non-relativistic hyperbolic Hilbert space with respect to the Born formula have been given by Kocik [18], Khrennikov [19,20], and Rochon and Tremblay [21]. Xuegang et al investigated the Dirac wave equation, Clifford algebraic spinors, a hyperbolic Hilbert space, and the hyperbolic spherical harmonics in hyperbolic spherical polar coordinates [22,23,24]. The hypercomplex numbers, and the geometries generated by these numbers, have been investigated by Catoni et al [25].…”
Section: Introductionmentioning
confidence: 99%
“…Its basis set {e 1 , e 2 , e 3 , e 4 } for Clifford product and inner product of It is obvious that the R 3,1 is a four-dimensional Minkowski space for inner product of Clifford algebra Cl 3,1 , which abbreviates R 3,1 as M 4 .…”
Section: Clifford Algebra and Four-dimensional Minkowski Spacementioning
confidence: 99%
“…In this work Hucks also found that the operations of C, P, and T on Dirac spinors are closely related to the three types of complex conjugation that exist when both hyperbolic and ordinary imaginary units are present. Xuegang et al investigated in this context the Dirac wave equation, Clifford algebraic spinors, a hyperbolic Hilbert space, and the hyperbolic spherical harmonics in hyperbolic spherical polar coordinates [11,12,13].…”
Section: Introductionmentioning
confidence: 99%